Contribution of columns in the seismic response of frames with intentionally eccentric braces - González Ureña, Andrés (2024)
Recent research showcases the novel Frame with Intentionally Eccentric Braces (FIEB) as a promising steel seismic-force-resisting system (SFRS) with the potential of becoming a viable alternative to the Concentrically Braced Frame (CBF), offering an improved seismic performance. The direct control over the structure’s strength at the target displacement level provided by the adjustable brace eccentricity renders FIEBs well suited to performance-oriented design and reduces incidental overstrength, resulting in cost-effective solutions. Additionally, the large post-elastic stiffness and partial self-centring capabilities of Braces with Intentional Eccentricity (BIEs) grant FIEBs an enhanced structural stability and make them suitable for use as the SFRS of high-rise buildings. However, to advance FIEBs to an implementable state, further research is required to properly understand all relevant aspects of their response, such as the contribution of the columns and the influence of employing different bracing configurations. In CBFs, columns contribute to the stability of the structure during earthquakes by distributing drift demands over the height of the building through bending. Aiming to ensure the conditions for this mechanism, the CSA S16 standard requires that columns in moderately ductile (MD) and limited-ductility (LD) CBFs be continuous and of constant cross-section over at least two storeys and be designed to withstand bending moments in the plane of the frame of 20% the flexural capacity of their cross-section, along with the combined gravity and brace-response-induced axial forces. Columns in FIEBs are expected to respond in a similar manner, but the relative weight of their contribution to the overall response has not yet been quantified, and whether the code requirements for columns in CBFs are adequate or need to be adapted must be verified. In this article, the contribution of columns in the seismic response of FIEBs is investigated. To this purpose, Non-Linear Response History Analysis is applied to FIEBs designed for combinations of number of storeys, two alternative bracing configurations (‘X’ and chevron with middle column), and columns arranged to bend about their major or minor axes. The influence of the braces and columns arrangement on the global response and the demands on the columns and their engagement in resisting the storey shears are assessed, and recommendations for design are proposed based on the obtained results.